Pengaruh Store Atmosphere dan Service Quality Terhadap Revisit Intention Konsumen Pada Golden Cafe dan Resto - Yolanda Yolanda; Rose Rahmidani (Universitas Negeri Padang, 2020)
The purpose of this research is to determine the effect of store atmosphere and service quality on customer revisit intention of Golden Cafe dan Resto at Kota Padang. This is the causative research. The population of the research is Padang city community. The number of research samples as many as 100 people and selected using purposive sampling technique. The data used is the primary data obtained through the distribution of questionnaires to Padang city community with established criteria. The analytical method is multiple regression analysis using SPSS 16. The results indicate that (1) Store atmosphere and service quality advertisements have a significant effect on revisit, (2) Store atmosphere has a significant effect on revisit intention, (3) Service quality have a significant influence on revisit intention. Kata Kunci: store atmosphere, service quality, revisit intention